Electrochemical Deposition and Formation Mechanism of Single-Crystalline Cu2O Octahedra on Aluminum - Q. T. Du; J. S. Tan; Q. T. Wang; C. Y. Li; X. H. Liu; R. S. Cai; Y. H. Ding; Y. Q. Wang (Journal of Analytical Methods in Chemistry)
A simple electrochemical deposition was developed to synthesize the cuprous oxide (Cu2O) octahedra on aluminum foils. The average edge length of the octahedra is about 300 nm. The chemical composition of the octahedra was determined using energy dispersive X-ray spectroscopy and electron energy-loss spectroscopy. The microstructure of the octahedra was investigated using transmission electron microscopy. The formation mechanism of the octahedra is proposed.